Immunotherapy as an approach to treating Alzheimer's disease - Morgan, David (Henry Stewart Talks, 2010)
Alzheimer's Disease, Immunization with amyloid-beta (A-beta), Radial arm water maze, Clinical trial of anti-A-beta vaccine, Mechanisms of antibody-mediated A-beta clearance, Catalytic fibril dissolution, Peripheral sink hypothesis, Systemic administration of anti-A-beta antibodies into old APP transgenic (Tg) mice, Diffuse and compact amyloid deposits, Systemic anti-A-beta antibody, Parenchymal and vascular amyloid deposits, Microhemorrhages, A possible solution to the problems of immunotherapy, Systemic administration experimental design, Intact and deglycosylated antibodies reverse cognitive decline, Current clinical trials of A-beta immunotherapy, Prospects for immunotherapy